Answer:
-4
Step-by-step explanation:
- y = 3(x+5)²-4
- y= 3(x²+10x+25)-4
- y= 3x²+30x+75-4
- y= 3x²+30x+71
Derivate the function
solve the equation y'= 0
- y'= 6x+30
- 6x+30= 0
- 6x= -30
- x = -5
The extrme value of y is reached in -5
y = 3(-5+5)²-4= -4
Answer:
E < F < G
Step-by-step explanation:
hope this helps
Y = 6x put it in a graphic calculator or go to desmos.com
Answer:
[-8c]⁻¹ = x
Step-by-step explanation:
-8xc = 1
____ ___
-8c -8c
![x = - \frac{1}{8c} \\ \\ or \\ \\ x = ({ -8c})^{-1}](https://tex.z-dn.net/?f=x%20%3D%20%20%20-%20%5Cfrac%7B1%7D%7B8c%7D%20%20%5C%5C%20%20%5C%5C%20or%20%5C%5C%20%20%5C%5C%20x%20%3D%20%28%7B%20-8c%7D%29%5E%7B-1%7D)
This, according to the Negative Exponential Rule [Reverse], is how you write this as a rational exponent. You bring the denominator to the numerator while ALTERING THE INTEGER SYMBOL FROM POSITIVE TO NEGATIVE:
b⁻ⁿ = 1\bⁿ
I am joyous to assist you anytime.